Implementation of hybrid nanofluid flowing in dimpled tube subjected to magnetic field - Tekir, Mutlu; Gedik, Engin; Arslan, Kami̇l; Gürdal, Mehmet; Pazarlıoğlu, Hayati Kadir; Altunay, Fethi Murat (Elsevier BV, 2022)
To pursue of enhancement convective heat transfer, both active and passive techniques have been elucidated simultaneously in this study. The effect of hybrid nanofluid flow in a dimpled tube implemented constant magnetic field (0 T ≤ B ≤ 0.3 T) to determine the convective heat transfer rate has not been investigated comparatively either numerically or experimentally, so far. Therefore, this study is the first study to elucidate the effect of hybrid nanofluid flow under the effect of a magnetic field at the fully developed hydrodynamic and developing thermally flow condition. Hydrothermal behavior of 1.0% vol. Fe3O4/H2O, 1.0% vol. Cu/H2O as mono nanofluid and 0.5% vol. Fe3O4–0.5% vol. Cu/H2O as hybrid nanofluid flow in the dimpled tube has been examined under constant heat flux boundary condition (q” = 4357 W/m2) and laminar flow regime (1131 ≤ Re ≤ 2102). As a result of experiments and numerical analyses, it is concluded that Nusselt number and friction factor have been enhanced using the magnetic field. Hybrid nanofluid flow in the dimpled tube implemented the magnetic field with the magnitude of 0.3 T causes to increase the Nusselt number and friction factor up to 11.87% and 6.19% for numerical, 174.65%, and 169.4% for experimental compared to the case of absence of a magnetic field, respectively.